The Path to Net Zero Emissions - Michael Hoel (Center for Economic Studies and ifo Institute (CESifo), 2024)
To reach the goals of the Paris agreement, net carbon emissions must be reduced to zero by the second half of this century. To achieve this, some kind of carbon dioxide removal (CDR) is needed. The paper gives an analysis of the interaction between extraction of fossil energy resources and CDR. If there is sufficient capacity for storing captured carbon, it will be optimal to have a period of negative net emissions. In this case cumulative extraction will not depend on climate costs, but will be higher the lower is the cost of CDR at low levels of CDR.
Keywords: Q35; Q40; Q54; 330; net zero emissions; negative emissions; carbon removal; CDR; CCS; stranded assets